«The Kingdom of Beauty»: Abkhazia in the Memoirs and Visual Arts Materials of the Department of Manuscripts of the Russian State Library - Krutova, M.S. (Âzyk i tekst, 2023)
The article is devoted to the analysis of little-known textual and pictorial materials with views of Abkhazia. The object of the research is the pictorial materials stored in the collection of the RSL Department of Manuscripts, the subject is drawings of coastal, mountain and urban landscapes of Abkhazia. The novelty of the study is determined by the fact that it introduces into scientific circulation, systematizes and comments on previously unpublished drawings with views of Abkhazia. Among the authors of drawings as professional artists of the second half of the XIX - beginning of the XX century (Zakhar Afanasievich Chuev, Mikhail Ilyich Bocharov, Alexander Alexandrovich Kiselyov), as well as amateurs who knew the technique of drawing well (Minister of War Dmitry Alexandrovich Milyutin). The revealed materials are analyzed using descriptive, biographical, comparative-historical and artistic-stylistic methods. It is concluded that the presented material expands the ideas of the authors who addressed the topic of the Caucasus. If professional artists tried to show the unusual beauty of the Caucasus and Abkhazia and capture those places that caused a special response in their soul, as well as convey their emotional feelings and experiences, then for an amateur artist D.A. Milyutin, in addition, drawings were necessary as illustrations for information about his official activities. The materials with views of Abkhazia identified in the Department of Manuscripts have practical value for a wide range of researchers studying the history and culture of Abkhazia. Further study of these materials opens up prospects for biographical, artistic-stylistic, figurative-artistic analysis for those researchers who study the creative and life path of the artists discussed in this article. The material will also be useful to philologists who draw parallels between works of verbal and visual art. Статья посвящена анализу малоизвестных изобразительных материалов с видами Абхазии. Объектом исследования являются изобразительные материалы, хранящиеся в собрании отдела рукописей РГБ, предметом - рисунки прибрежных, горных и городских пейзажей Абхазии. Новизна исследования определяется тем, что в нем вводятся в научный оборот, систематизируются и комментируются ранее не публиковавшиеся рисунки с видами Абхазии. Среди авторов рисунков как профессиональные художники второй половины XIX - начала XX века (Захар Афанасьевич Чуев, Михаил Ильич Бочаров, Александр Александрович Киселев), так и любители, которые хорошо владели техникой рисунка (военный министр Дмитрий Александрович Милютин). Выявленные материалы проанализированы с использованием описательного, биографического, сравнительно-исторического и художественно-стилистического методов. Сделан вывод о том, что представленный материал расширяет представления об авторах, обращавшихся к теме Кавказа. Если художники-профессионалы старались показать необычную красоту Кавказа и Абхазии и запечатлеть те места, которые вызвали особый отклик в их душе, а также передать свои эмоциональные ощущения и переживания, то для художника-любителя Д.А. Милютина, помимо этого, рисунки были необходимы в качестве иллюстраций к информации об его служебной деятельности. Выявленные в Отделе рукописей материалы с видами Абхазии имеют практическую ценность для широкого круга исследователей, изучающих историю и культуру Абхазии. Дальнейшее изучение этих материалов открывает перспективы для биографического, художественно-стилистического, образно-художественного анализа тем исследователям, которые изучают творческий и жизненный путь художников, о которых шла речь в данной статье. Материал будет полезен и филологам, проводящим параллели между произведениями словесного и изобразительного искусства.